Thunderclap headache in children - Carvalho, Fabiane Caxias de Paula; Menezes, Letícia Soares Teles De; Matos, Larissa Silva de Oliveira; Santos, Ana Flávia Resende; Martins, Lorena do Carmo de Souza; Almeida, Rodrigo Franklin Pinheiro (Headache Medicine, 2023)
Full abstract in PDF.